Associations between lower systolic blood pressure threshold, Alzheimer's disease and vascular dementia among very old adults: Epidemiology / Prevalence, incidence, and outcomes of MCI and dementia. (7th December 2020) - Park, Christina; Hajat, Anjum; Leary, Cindy S; Adam, Claire; Semmens, Erin O; Kaufman, Joel D; Fitzpatrick, Annette L
Abstract: Background: Increasing evidence supports the contribution of hypertension to the risk of Alzheimer's disease (AD) and vascular dementia (VaD). The objective of this paper is to examine whether the risk of AD and VaD is associated with a lower threshold of systolic blood pressure (SBP) than the traditional level of ≥140 mmHg. Methods: Using data from the Ginkgo Evaluation of Memory Study (GEMS), we obtained baseline SBP measurements from 3, 068 participants who were dementia‐free at enrollment. Cognition was evaluated every 6 months over 8 years; dementia and its subtypes were adjudicated by a panel of neurologists. Cutoff values for continuous SBP were estimated by the maximum Youden index (sensitivity + specificity ‐ 1) for AD (without VaD) and VaD (with or without AD). The performance of the estimated SBP cutoff values was compared with the traditional SBP threshold of 140 mmHg using the area under the receiver operating characteristic curve (AUC). Based on the estimated cutoffs, we dichotomized SBP, created Kaplan‐Meier survival curves, and calculated hazard ratios (HRs) for AD and VaD incidence using Cox proportional hazards models, adjusted for age, gender, race, education and baseline depression. Results: The mean (± SD) age of participants was 78.6 (± 3.3) years and 46% were female. According to the Youden index, the optimal SBP cutoff values for capturing AD and VaD were 122 (sensitivity: 74.2%; specificity: 27.6%) and 131 mmHg (sensitivity: 67.3%; specificity: 47.6%), respectively. Although these estimates for SBP cutoffs were not significantly different from AUC estimates for the traditional cutoff, a greater risk of VaD at the optimized threshold (131 mmHg) was found (Figure 1, Kaplan‐Meier analysis and log‐rank test P <0.001). Using Cox models, we found that SBP ≥131 mmHg was associated with a 70% increased risk of VaD (HR:1.71, 95% CI:1.21, 2.43; P = 0.002). We did not observe an association between SBP cutoff of 122 and AD incidence. Conclusion: A lower SBP threshold was identified in relation to risk of VaD while associations with AD were inconclusive. Further study is needed to evaluate the accuracy of lower SBP cutoff values in identifying AD and VaD in other populations.